2022
DOI: 10.3389/falgy.2022.941020
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Impact of Food Immunotherapy on Health-Related Quality of Life in Clinical Trials

Abstract: Food allergy is a common, and often lifelong, disorder with considerable negative impact on the quality of life of those affected and their families. While several promising immunotherapies for food allergy have either been approved or are in late-phase clinical trials based on demonstrated effectiveness at inducing desensitization, evidence of benefit in terms of improving patient-centered outcomes is inconsistent. Historically, health-related quality of life has not been prioritized as an endpoint in food im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…Unfortunately, only one study investigated the effect of birch pollen AIT on the patient-reported outcome “FA-QoL” using the validated FAQLQ-AF questionnaire and showed that there was no significant difference between patients receiving SCIT or placebo at endpoint ( 11 ). As the primary burden on patients living with food allergy is a reduced QoL, treatment success in trials should also be defined by an improved QoL ( 25 , 26 ). Future studies, investigating the effect of birch pollen AIT on BPFA, should therefore include QoL as an outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, only one study investigated the effect of birch pollen AIT on the patient-reported outcome “FA-QoL” using the validated FAQLQ-AF questionnaire and showed that there was no significant difference between patients receiving SCIT or placebo at endpoint ( 11 ). As the primary burden on patients living with food allergy is a reduced QoL, treatment success in trials should also be defined by an improved QoL ( 25 , 26 ). Future studies, investigating the effect of birch pollen AIT on BPFA, should therefore include QoL as an outcome.…”
Section: Discussionmentioning
confidence: 99%
“…While strict avoidance of the allergen is currently the only effective treatment, immunotherapy has been recognised as a potentially effective therapeutic strategy for treating food allergies. The success of immunotherapy is dependent on identifying the most promising targets for immune modulation and developing effective strategies to target them (Hwang et al, 2022;Lloyd et al, 2022).…”
Section: Promising Targets For Immunotherapies In Food Allergy: Effec...mentioning
confidence: 99%